A biobased degradable meal box material and a preparation method thereof

CN122898110APending Publication Date: 2026-10-13HANYANBO BIOTECHNOLOGY (JIANGSU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611144620.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

但上述方法仍主要依赖化学键合或弱物理作用,界面增强效果有限,且在长期使用或热加工过程中容易发生界面失效

Benefits of technology

通过在植物纤维表面引入经酶促生物矿化原位生长的纳米碳酸钙晶须,并使其以特定取向嵌入纤维细胞壁浅层及可降解聚酯基体内部,形成跨越两相界面的机械锚固结构,使植物纤维与聚酯基体之间由传统弱界面作用转变为稳定的机械互锁作用,从而显著提高界面结合强度与应力传递效率;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898110A_ABST
    Figure CN122898110A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of bio-based polymer composite materials, and particularly relates to a bio-based degradable meal box material and a preparation method thereof.The technical scheme comprises that the material comprises a degradable polyester matrix and a plant fiber reinforced phase, the plant fiber reinforced phase is modified reinforced plant fiber with nano calcium carbonate whiskers loaded in situ on the surface through enzymatic biomimetic mineralization, the nano calcium carbonate whiskers are mainly in vertical orientation, the root part is embedded in the shallow layer of the cell wall of the plant fiber, the end part is exposed and embedded in the degradable polyester matrix, and a mechanical locking structure across the interface is formed.During preparation, the fiber is first activated and pretreated, then modified in situ through enzymatic biomimetic mineralization to obtain modified reinforced plant fiber, then blended, extruded and granulated, and finally hot-pressed to obtain a meal box finished product.The present application significantly improves the mechanical strength, toughness and thermal stability of the composite material while maintaining full biodegradability, and the mild aqueous preparation process is easy to implement in industrialization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of bio-based polymer composite materials technology, and in particular to a bio-based biodegradable lunchbox material and its preparation method. Background Technology

[0002] With the increasing use of disposable plastic lunch boxes, traditional petroleum-based polyolefin materials are difficult to degrade in the natural environment, easily causing white pollution. Therefore, bio-based biodegradable polyester materials, represented by polylactic acid (PLA), polyhydroxyalkanoates (PHA), polybutylene succinate (PBS), and their blends, are gradually being applied in the food packaging field. However, existing bio-based polyester materials generally suffer from insufficient toughness, poor impact resistance, and low heat distortion temperature, limiting their further application in structural load-bearing products such as lunch boxes.

[0003] To address these issues, existing technologies typically employ plant fibers as reinforcement to modify polyester materials, such as wheat straw fiber, rice straw fiber, or bamboo fiber. However, due to the strong hydrophilicity of plant fibers and the hydrophobicity of the biodegradable polyester matrix, a significant polarity difference exists at the interface, resulting in poor interfacial compatibility and weak interfacial bonding. Under external forces, interfacial debonding or pull-out often occurs between the fibers and the matrix, thus limiting the improvement of the overall mechanical properties of the composite material.

[0004] To improve interfacial properties, existing technologies typically employ methods such as silane coupling agents, maleic anhydride grafted compatibilizers, or surface-coated inorganic particles to modify plant fibers. However, these methods still primarily rely on chemical bonding or weak physical interactions, resulting in limited interfacial enhancement effects and a tendency for interfacial failure during long-term use or thermal processing.

[0005] Furthermore, while existing inorganic fillers (such as calcium carbonate particles) can improve material rigidity, they are mostly granular filler structures, making it difficult to form effective mechanical transfer paths across interfaces, and their synergistic reinforcement effect between fibers and the matrix is ​​insufficient.

[0006] Therefore, there is an urgent need for a new reinforcement method that can construct a stable and high-strength interfacial connection structure between plant fibers and biodegradable polyester matrix, so as to improve the mechanical properties and interfacial stability of the material without affecting its biodegradability. Summary of the Invention

[0007] The purpose of this invention is to address the problems existing in the background art by proposing a bio-based biodegradable lunchbox material and its preparation method.

[0008] To achieve the above objectives, the present invention provides the following technical solution: a bio-based biodegradable lunch box material, comprising a biodegradable polyester matrix and a plant fiber reinforcing phase, wherein the plant fiber reinforcing phase is a modified reinforcing plant fiber whose surface has been enzymatically biomineralized and in-situ loaded with nano-calcium carbonate whiskers; The nano-calcium carbonate whiskers mainly grow in an orientation perpendicular to the surface of the plant fiber, and the roots of the nano-calcium carbonate whiskers are embedded in the shallow cell wall of the plant fiber, while the ends are exposed on the fiber surface and embedded in the biodegradable polyester matrix, so that a cross-interface mechanical locking structure is formed between the plant fiber and the biodegradable polyester matrix.

[0009] Furthermore, by weight, it includes 60-85 parts of biodegradable polyester matrix, 10-30 parts of the modified reinforced plant fiber, and 3-10 parts of food-grade processing aids.

[0010] Furthermore, the biodegradable polyester matrix is ​​any one or more blends of polyhydroxyalkanoates, polybutylene succinate, and polybutylene adipate; the blend is obtained by compounding polyhydroxyalkanoates and polybutylene adipate at a mass ratio of 3 to 5:1.

[0011] Furthermore, the plant fiber is any one of wheat straw fiber, rice straw fiber, and bamboo pulp fiber, with a fiber length of 0.5~3mm; the nano-calcium carbonate whiskers are aragonite-type calcium carbonate whiskers with a diameter of 20~80nm, a length of 100~500nm, and a loading of 8%~20% of the dry weight of the plant fiber; and the length of the nano-calcium carbonate whisker end embedded in the biodegradable polyester matrix is ​​30%~90% of the total whisker length.

[0012] Furthermore, the food-grade processing aid includes at least one of plasticizer, lubricant, and antioxidant; the plasticizer is tributyl acetyl citrate, the lubricant is palm wax or soybean wax, and the antioxidant is vitamin E.

[0013] A method for preparing a bio-based biodegradable lunchbox material includes the following steps: S1. Fiber activation pretreatment: Plant fibers are heated in an alkaline solution to remove some lignin and hemicellulose. After washing with water to neutrality, they are dried to obtain activated plant fibers. S2. Enzyme-catalyzed in-situ mineralization modification: Activated plant fibers are dispersed in a buffer solution containing carbonic anhydrase, carbon dioxide gas is introduced under constant temperature stirring, and soluble calcium salt solution is added dropwise at a uniform rate. After the reaction is completed, the fibers are filtered, washed, and dried to obtain modified and reinforced plant fibers with nano-calcium carbonate whiskers loaded on the surface. S3. Blending and extrusion granulation: The biodegradable polyester matrix, modified reinforcing plant fiber and processing aid are mixed evenly according to the ratio, fed into a twin-screw extruder for melt blending, and then extruded and granulated to obtain composite granules. S4. Hot pressing molding: The composite granules are added into the lunch box mold, and then hot-pressed, cooled and demolded to obtain the bio-based biodegradable lunch box product.

[0014] Furthermore, in step S2, the buffer solution containing carbonic anhydrase is a Tris-HCl buffer with a pH of 7.5-8.5, and the concentration of carbonic anhydrase is 0.5-2 g / L; the soluble calcium salt is calcium chloride or calcium acetate, and the concentration of the calcium salt solution is 0.1-0.5 mol / L; the reaction temperature is 25-40℃, and the reaction time is 2-6 h; in addition, a soluble organic template agent is added to the reaction system, the template agent being polyaspartic acid or its sodium salt, to induce the directional growth of aragonite-type calcium carbonate whiskers.

[0015] Furthermore, in step S1, the alkaline solution is a sodium hydroxide solution with a mass fraction of 2% to 5%, the treatment temperature is 80 to 90°C, and the treatment time is 1 to 3 hours.

[0016] Furthermore, in S3, the temperature of each section of the twin-screw extruder is 130~160℃, and the screw speed is 150~250rpm; in S4, the hot pressing temperature is 140~170℃, the molding pressure is 8~15MPa, and the holding time is 30~90s.

[0017] Compared with the prior art, the beneficial effects of the present invention are as follows: By introducing enzymatically biomineralized in-situ grown nano-calcium carbonate whiskers onto the surface of plant fibers and embedding them in the shallow layer of fiber cell walls and the interior of biodegradable polyester matrix in a specific orientation, a mechanical anchoring structure spanning the two-phase interface is formed, transforming the traditional weak interfacial interaction between plant fibers and polyester matrix into a stable mechanical interlocking interaction, thereby significantly improving the interfacial bonding strength and stress transfer efficiency. Nano-calcium carbonate whiskers form a high-density three-dimensional physical bridging network in the interface region, which effectively inhibits fiber pull-out and interface debonding, significantly improving the tensile strength, flexural modulus and impact toughness of the composite material, while also improving the energy dissipation capacity of the material during loading. The surface roughness of plant fibers after alkali activation and in-situ mineralization treatment is improved, and they have a large number of micro-nano scale structures, which is conducive to the full wetting and coating of molten polyester matrix, and improves the interfacial contact area and structural stability. The plant fibers, calcium carbonate whiskers, and food-grade processing aids introduced are all environmentally friendly materials that do not affect the biodegradation pathway of the polyester matrix, enabling the composite material to achieve efficient degradation under industrial composting conditions while improving its mechanical properties. The process employs an enzyme-catalyzed in-situ mineralization method to complete whisker growth under mild aqueous conditions, avoiding high temperature, high pressure, or highly corrosive chemical environments. The process is easy to control and is compatible with existing twin-screw extrusion and hot pressing processes, enabling industrial-scale production. Attached Figure Description

[0018] Figure 1 This is a schematic diagram of the method flow of the present invention. Detailed Implementation

[0019] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0020] The core concept of this invention lies in the in-situ growth of specifically oriented nano-calcium carbonate whiskers on the surface of plant fibers using enzymatic biomineralization technology, constructing a cross-scale three-phase mechanically interlocked interface structure of "fiber-whisker-matrix". Specifically, carbonic anhydrase catalyzes the CO2 hydration reaction, mildly and controllably generating carbonate ions on the fiber surface, which then combine with calcium ions. Under the synergistic induction of a polyaspartic acid template agent, heterogeneous nucleation occurs in the shallow pores and surface of the plant fiber cell wall, resulting in the directional growth of aragonite-type nano-calcium carbonate whiskers. The roots of these whiskers are physically interlocked with the loose layer and nanoscale pores of the fiber cell wall, forming the first-level anchoring point. The whisker ends are exposed on the fiber surface and oriented in a direction approximately normal to the fiber surface. During subsequent melt blending with a biodegradable polyester matrix, the exposed whisker ends are fully wetted and embedded in the molten polyester matrix, forming the second-level anchoring point. In this way, a single whisker achieves bidirectional anchoring across the interface between the plant fiber and the polyester matrix. The synergistic effect of a large number of whiskers forms a dense three-dimensional physical interlocking network at the interface—a "cross-interface mechanical interlocking structure." This structure fundamentally solves the problem of interfacial delamination between plant fibers and the polymer matrix caused by polarity differences. It upgrades the interfacial interactions in traditional fiber-reinforced composites, which are mainly based on weak hydrogen bonds and van der Waals forces, to a strong interfacial anchoring mechanism dominated by mechanical interlocking. This significantly improves the mechanical strength and thermal stability of the composite material while retaining its fully biodegradable properties.

[0021] The present invention will be further described in detail below with reference to specific embodiments, such as Figure 1As shown. It should be understood that the specific embodiments described herein are only for explaining the present invention and are not intended to limit the scope of protection of the present invention. Unless otherwise specified, all raw materials and reagents used in the present invention can be obtained through commercial channels or synthesized according to conventional methods in the art.

[0022] Example 1

[0023] S1, Fiber activation pretreatment 100g (octane-dry weight) of wheat straw fibers with a length of approximately 0.5–3 mm was selected and immersed in 2L of a 3% sodium hydroxide solution. The solution was then heated and stirred in an 85°C water bath for 2 hours. This step aims to selectively remove some lignin and hemicellulose from the fiber cell walls, promoting fiber bundle dispersion and increasing specific surface area. Simultaneously, it roughens the fiber surface and significantly increases the number of surface hydroxyl groups. More importantly, it forms numerous nano- to submicron-sized pores and groove-like defects in the shallow layer (approximately 50–500 nm depth) of the originally dense fiber cell walls. These active particles provide natural templates and anchoring points for the heterogeneous nucleation and root embedding of calcium carbonate whiskers in subsequent steps. After the reaction, the fibers were repeatedly washed with deionized water until the pH of the washing solution was neutral. The fibers were then dried in a 60°C vacuum drying oven to constant weight to obtain activated plant fibers.

[0024] S2, Enzyme-catalyzed in-situ mineralization modification Preparation of the carbonic anhydrase-containing buffer: Add 1.0 g of carbonic anhydrase (CA) to 1 L of pH 8.0 Tris-HCl buffer and gently stir until completely dissolved to obtain an enzyme buffer with a concentration of 1.0 g / L. The Tris-HCl buffer system is used to maintain a stable pH during the reaction process, ensuring that the carbonic anhydrase remains in a highly active conformational state.

[0025] Preparation of template agent and calcium salt mixed solution: Dissolve 0.5g of sodium polyaspartate (PASP) in 500mL of deionized water, then add 55.5g of anhydrous calcium chloride, stir to dissolve, and prepare a stock solution with a calcium chloride concentration of 1.0mol / L for later use.

[0026] Biomineralization reaction: All activated plant fibers obtained in step S1 were dispersed in the above-mentioned buffer solution containing carbonic anhydrase, heated to 30°C and stirred at a constant temperature. Carbon dioxide gas was continuously introduced into the reaction system at a partial pressure of 0.1 MPa, while the above-mentioned calcium chloride stock solution was added dropwise at a rate of 1.5 mL / min using a peristaltic pump. The core reaction mechanism of this step is that carbonic anhydrase (CA) is one of the most efficient enzymes known in nature, with each active site capable of catalyzing approximately 10 [units of enzyme name missing] per second. 6 One CO2 molecule hydrates and is converted into HCO3. - HCO3 -It further ionizes to produce CO3 under alkaline conditions. 2- Compared to the traditional chemical precipitation method of directly adding carbonates, the enzyme catalytic pathway precisely controls CO3. 2- The formation rate is maintained at a stable and moderate supersaturation level at the solid-liquid interface on the fiber surface, thus effectively avoiding explosive nucleation and homogeneous precipitation in the bulk solution, allowing calcium carbonate nucleation events to preferentially occur on the fiber surface and in shallow pores. Simultaneously, sodium polyaspartate, as a soluble organic template agent, plays a dual regulatory role: firstly, the carboxyl and amide groups on its molecular chain can selectively adsorb onto specific crystal faces of the aragonite crystal form, reducing the growth rate of those faces, thereby inducing calcium carbonate to precipitate as the aragonite phase (acicular / whisker-like) rather than the thermodynamically more stable calcite phase (rhombohedral granular); secondly, its macromolecular framework forms a negatively charged quasi-liquid template layer on the fiber surface, guiding the aragonite nuclei to preferentially grow in the lowest energy orientation—that is, perpendicular to the fiber surface. Through the synergistic effect of "enzymatic slow carbon supply + dual regulation of PASP crystal form and orientation", calcium carbonate, in the form of aragonite nanocrystals, heterogeneously nucleates and grows directionally along the fiber surface. The whisker roots actively embed themselves into the shallow pores of the cell wall created in step S1 as the growth front advances. After the reaction continues for 4 hours, aeration and dripping are stopped, and stirring and aging are continued for another 30 minutes to fully perfect the whisker structure.

[0027] Post-processing: The fiber suspension was filtered and washed repeatedly with deionized water to remove free enzymes, residual salt ions and unfixed calcium carbonate particles. Finally, it was dried in a forced-air dryer at 80°C to obtain modified and reinforced plant fibers with aragonite-type nano-calcium carbonate whiskers uniformly loaded on the surface.

[0028] Characterized by field emission scanning electron microscopy (SEM) and transmission electron microscopy (TEM), the nano-calcium carbonate whiskers obtained in this embodiment have a diameter of approximately 40–60 nm, a length of approximately 200–400 nm, and an aspect ratio of approximately 5–8. The orientation angle between the whiskers and the fiber surface is mainly distributed between 70° and 90°, statistically exhibiting a significant vertical orientation characteristic. High-resolution TEM observation clearly shows that the whisker roots penetrate deep into the loose layer and pores formed by alkali treatment of the fiber cell wall, with an embedding depth of approximately 50–200 nm. No obvious interface gap was observed between them, indicating the formation of a strong mechanical anchor. Thermogravimetric analysis (TGA) determined that the loading of the nano-calcium carbonate whiskers is approximately 15% of the dry weight of the plant fiber.

[0029] Example 2

[0030] This embodiment is basically the same as Embodiment 1, except that: the plant fiber used in step S1 is bamboo pulp fiber; in step S2, the carbonic anhydrase concentration is 2.0 g / L, the reaction temperature is 35℃, the reaction time is 3 h, and the template agent is polyaspartic acid. The aragonite-type nano-calcium carbonate whiskers loaded on the obtained modified and reinforced plant fiber have a diameter of approximately 50-80 nm, a length of approximately 150-350 nm, and a loading of approximately 12% of the fiber dry weight. After treatment with this method, the bamboo pulp fiber exhibits particularly good uniformity in the distribution of whiskers on the fiber surface. This is attributed to the fact that the bamboo pulp fiber has been initially fibrillated during the pulping process, and the surface active sites are more abundant and uniform after alkali activation.

[0031] Example 3

[0032] This embodiment is basically the same as Embodiment 1, except that: the plant fiber used in step S1 is rice straw fiber, and the alkaline treatment time is 3 hours; in step S2, the soluble calcium salt used is calcium acetate with a concentration of 0.3 mol / L, which is added dropwise at a rate of 3 mL / min using a peristaltic pump. The loading of aragonite-type nano-calcium carbonate whiskers on the obtained modified and reinforced plant fiber is approximately 18% of the fiber's dry weight. The higher whisker loading allows it to provide a higher density of interfacial anchor points during subsequent composite processes, making it suitable for applications requiring higher rigidity.

[0033] Example 4

[0034] S3, Blending Extrusion Granulation The following components, after drying, were weighed by weight: 75 parts of a blend serving as the biodegradable polyester matrix (premixed in a high-speed mixer by a mass ratio of 4:1 of polyhydroxyalkanoate (PHA) and polybutylene adipate / terephthalate (PBAT)); 20 parts of the modified reinforced plant fiber prepared in Example 1; and 5 parts of food-grade processing aids (including 3.5 parts of the plasticizer acetylthiate tributyl citrate, 1 part of the lubricant palm wax, and 0.5 parts of the antioxidant vitamin E). The plasticizer acetylthiate tributyl citrate (ATBC) is a bio-based, non-toxic plasticizer used to improve the brittleness of PHA and reduce processing temperature; palm wax, as a naturally derived lubricant, reduces the coefficient of friction between the melt and the metal surface, which is beneficial for fiber dispersion and demolding; vitamin E is a natural antioxidant that inhibits thermo-oxidative degradation during processing and protects the integrity of the molecular chains.

[0035] All components were added to a high-speed mixer and mixed at 500 rpm for 10 minutes at room temperature to obtain a homogeneous premix. The premix was then fed into a co-rotating parallel twin-screw extruder for melt blending extrusion. The temperatures of each section of the extruder from the feed section to the die head were set sequentially to 135℃, 145℃, 155℃, 155℃, and 150℃, and the screw speed was set to 200 rpm. During the melt blending process, the biodegradable polyester matrix fully impregnated and encapsulated the modified reinforcing plant fibers. Under the combined action of the shear and stretching flow fields of the twin screw, the molten polyester molecular chains were forced into the gaps between the whisker clusters on the fiber surface. The exposed ends of the nano-calcium carbonate whiskers on the fiber surface (accounting for approximately 30% to 90% of the total length, corresponding to an embedding depth of approximately 60 to 360 nm) were fully inserted and embedded into the interior of the polyester matrix under the dual drive of melt hydrodynamic pressure and interfacial capillary force. After being water-cooled and air-dried, the extruded strips are cut into cylindrical composite granules with a diameter of 2-3 mm by a pelletizer.

[0036] S4, Hot pressing molding for box making After accurately weighing the composite granules obtained in step S3, they are added to the preheated mold cavity of the lunchbox. The mold temperature is controlled at 165℃ for the upper mold and 160℃ for the lower mold. A molding pressure of 12MPa is applied when the mold is closed, and this pressure is held for 60 seconds. The holding pressure stage is a critical window period for the final shaping of the interfacial locking structure: under the continuous action of heat and pressure, the polyester melt further fills the microscopic voids around the whiskers, ensuring that each stress-bearing whisker is tightly wrapped by the matrix. After the holding pressure is completed, cooling water is circulated through the mold to cool it down to below 60℃. The mold is then opened and the product is ejected, resulting in a light yellow bio-based biodegradable lunchbox with a natural fiber texture.

[0037] In this finished product, SEM observation of the liquid nitrogen brittle fracture surface confirmed that the interface between the modified reinforced plant fiber and the PHA / PBAT polyester matrix was blurred, with very few fiber pull-out voids. Instead, there was large-area plastic deformation of the matrix and fiber tearing. High-magnification SEM clearly showed that the roots of the nano-calcium carbonate whiskers were anchored within the fiber cell walls, while the ends were embedded in the polyester matrix. Individual whiskers formed physical bridges across the fiber / matrix interface, and a large number of whiskers were arranged collaboratively to form a dense and uniformly oriented "cross-interface mechanical interlocking structure." This structure is microscopically similar to the "rebar anchoring" effect in engineering—the whiskers act like micron-sized anchors, with one end rooted in the fiber "foundation" and the other end embedded in the polyester "concrete," transforming the macroscopically clear boundary between the two phases into a gradient interlocking zone with a continuous stiffness transition. This cross-scale physical interlocking morphology, unlike traditional chemical bonding or simple physical adsorption, greatly improves the efficiency of interfacial stress transmission. Moreover, when subjected to external loads, the energy consumption of whisker pull-out and the energy consumption of matrix plastic deformation constitute a dual energy dissipation mechanism, giving the material excellent impact toughness.

[0038] Example 5

[0039] This embodiment is basically the same as Example 4, except that: the biodegradable polyester matrix is ​​80 parts of polybutylene succinate (PBS), the modified reinforcing plant fiber is 15 parts of the bamboo pulp fiber-based reinforcing phase prepared in Example 2, and the processing aid is 5 parts. The hot pressing temperature is 145℃, and the pressure is 10MPa. PBS has a lower melting point and better processing fluidity than PHA / PBAT blends; therefore, appropriately reducing the molding temperature and pressure can achieve good interfacial wetting and locking.

[0040] Example 6

[0041] This embodiment is basically the same as Example 4, except that: the biodegradable polyester matrix is ​​70 parts of a blend of PHA and PBAT in a mass ratio of 3:1; the modified reinforcing plant fiber is 25 parts of the rice straw fiber-based reinforcing phase prepared in Example 3; and the processing aid is 5 parts. In this embodiment, the proportion of PHA is relatively reduced and the proportion of PBAT is relatively increased, which is beneficial to processing toughness; at the same time, the fiber filling amount is increased to 25 parts, the density of whisker anchor points is increased, and the material stiffness is further improved, making it suitable for deep-cavity lunch box products with higher stiffness requirements.

[0042] Comparative Example 1 The difference from Example 4 is that the plant fibers activated in step S1 were used, but the enzymatic in-situ mineralization modification in step S2 was not performed; they were directly used for blending extrusion in S3 and hot pressing in S4. This comparative example is used to quantify the net contribution of the introduction of the "cross-interface mechanical interlocking structure" to the overall performance of the composite material.

[0043] Comparative Example 2 The difference from Example 4 is that the soluble organic template agent sodium polyaspartate was not added in step S2, while other conditions remained the same. The calcium carbonate deposited on the surface of the resulting fiber was mainly irregular granular calcite (confirmed by XRD), with a particle size of about 100~300nm, almost no whisker morphology, and the particles only exhibited weak physical adsorption to the fiber surface, resulting in poor bonding force.

[0044] Comparative Example 3 The difference from Example 4 is that the plant fibers activated in step S1 are used, but the S2 treatment is omitted. Instead, the fibers are impregnated in an ethanol solution with 2% (by weight of fiber) of silane coupling agent KH-550, and then dried before being used for subsequent blending. This comparative example is used to compare the differences in enhancement efficiency and reliability between the "physical bonding interface" of this invention and the traditional "chemical bonding interface".

[0045] The composite material granules obtained in Examples 4-6 and Comparative Examples 1-3 were injection molded into standard test strips according to the corresponding standards, and their mechanical properties, thermal properties, and degradation properties were tested. The test results are shown in the table below.

[0046] Comparison of material properties between each embodiment and the comparative example

[0047] As can be seen from the table above: The overall mechanical properties of Examples 4-6 of this invention are far superior to those of the comparative examples. Compared with Comparative Example 1 (unmineralized), the tensile strength, flexural modulus, and impact strength of Example 4 are increased by approximately 73%, 100%, and 107%, respectively. This fully demonstrates that the introduction of the "cross-interface mechanical interlocking structure" is the main reason for the performance improvement, rather than fiber activation itself. Compared with Comparative Example 2 (without PASP), the performance of Example 4 is also significantly improved, strongly demonstrating that the PASP template agent is a key regulatory factor inducing the growth of aragonite whiskers and their vertical orientation, and that simple granular calcium carbonate cannot form an effective cross-interface anchoring. Compared with Comparative Example 3 (conventional silane coupling agent), the technical solution of this invention improves the tensile strength, flexural modulus, and impact strength by approximately 25%, 31%, and 31%, respectively, indicating that cross-scale physical-mechanical interlocking has higher reinforcement efficiency and better reliability than chemically bonded interfacial modification in natural fiber / polyester systems.

[0048] The heat distortion temperature (HDT) of Examples 4-6 all reached above 112°C, significantly better than the comparative examples. This is due to the effective suppression of thermal expansion mismatch and slippage at the fiber / matrix interface by the whisker anchoring network at high temperatures, enabling the composite material to maintain good rigidity under thermal loads.

[0049] The 90-day industrial compost degradation rate of all embodiments exceeded 90%, indicating that the introduction of whisker inorganic phase and PASP template agent did not affect the inherent biodegradability of the biodegradable polyester matrix. The material fully retains its biodegradable characteristics while giving it excellent performance, thus meeting the requirements of circular economy and environmental protection.

[0050] The food contact containers obtained in Examples 4-6 were subjected to total migration and specific migration tests for food contact materials according to GB 9685 and EU 10 / 2011 standards, and the results all met the limit requirements. The carbonic anhydrase, sodium polyaspartate, ATBC, palm wax, and vitamin E used in this invention are all non-toxic or low-toxic substances permitted for use in food contact materials. Furthermore, no harmful residues were observed after the multi-stage washing in step S2 and the high-temperature processing in step S3, demonstrating their safety as disposable food packaging materials.

[0051] Comprehensive comparison shows that this invention, through a three-pronged technical approach of "alkali activation pore formation + enzymatic mineralization + dual regulation of PASP crystal form and orientation," successfully constructs a "cross-interface mechanical locking structure" on the surface of plant fibers, mediated by vertically oriented aragonite-type nano-calcium carbonate whiskers. This structure creates a strong anchoring interface between the natural plant fibers and the biodegradable polyester matrix, similar to "reinforced concrete reinforcement," significantly improving the mechanical and thermal properties of the material while retaining its fully biodegradable environmentally friendly attributes. This resolves the long-standing technical contradiction in the field of bio-based composite materials: the incompatibility between "interface reinforcement and full degradation."

[0052] The above specific embodiments are merely several further embodiments of the present invention. Based on the technical solutions of the present invention and the relevant teachings of the above embodiments, those skilled in the art can make various alternative improvements and combinations to the above specific embodiments.

[0053] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

Claims

1. A bio-based biodegradable lunchbox material, comprising a biodegradable polyester matrix and a plant fiber reinforcing phase, characterized in that: The plant fiber reinforcing phase is a modified reinforcing plant fiber with nano-calcium carbonate whiskers loaded in situ through enzymatic biomineralization on its surface. The nano-calcium carbonate whiskers mainly grow in an orientation perpendicular to the surface of the plant fiber, and the roots of the nano-calcium carbonate whiskers are embedded in the shallow cell wall of the plant fiber, while the ends are exposed on the fiber surface and embedded in the biodegradable polyester matrix, so that a cross-interface mechanical locking structure is formed between the plant fiber and the biodegradable polyester matrix.

2. The bio-based biodegradable lunchbox material according to claim 1, characterized in that: By weight, it includes 60-85 parts of biodegradable polyester matrix, 10-30 parts of the modified and reinforced plant fiber, and 3-10 parts of food-grade processing aids.

3. The bio-based biodegradable lunchbox material according to claim 1, characterized in that: The biodegradable polyester matrix is ​​any one or more blends of polyhydroxy fatty acid ester, polybutylene succinate, and polybutylene adipate-terephthalate; the blend is obtained by compounding polyhydroxy fatty acid ester and polybutylene adipate-terephthalate at a mass ratio of 3 to 5:

1.

4. The bio-based biodegradable lunchbox material according to claim 1, characterized in that: The plant fiber is any one of wheat straw fiber, rice straw fiber, and bamboo pulp fiber, with a fiber length of 0.5~3mm; the nano-calcium carbonate whiskers are aragonite-type calcium carbonate whiskers with a diameter of 20~80nm, a length of 100~500nm, and a loading of 8%~20% of the dry weight of the plant fiber; and the length of the nano-calcium carbonate whisker end embedded in the biodegradable polyester matrix is ​​30%~90% of the total whisker length.

5. The bio-based biodegradable lunchbox material according to claim 2, characterized in that: The food-grade processing aid includes at least one of plasticizer, lubricant, and antioxidant; the plasticizer is tributyl acetyl citrate, the lubricant is palm wax or soybean wax, and the antioxidant is vitamin E.

6. A method for preparing a bio-based biodegradable lunchbox material, characterized in that, Includes the following steps: S1. Fiber activation pretreatment: Plant fibers are heated in an alkaline solution to remove some lignin and hemicellulose. After washing with water to neutrality, they are dried to obtain activated plant fibers. S2. Enzyme-catalyzed in-situ mineralization modification: Activated plant fibers are dispersed in a buffer solution containing carbonic anhydrase, carbon dioxide gas is introduced under constant temperature stirring, and soluble calcium salt solution is added dropwise at a uniform rate. After the reaction is completed, the fibers are filtered, washed, and dried to obtain modified and reinforced plant fibers with nano-calcium carbonate whiskers loaded on the surface. S3. Blending and extrusion granulation: The biodegradable polyester matrix, modified reinforcing plant fiber and processing aid are mixed evenly according to the ratio, fed into a twin-screw extruder for melt blending, and then extruded and granulated to obtain composite granules. S4. Hot pressing molding: The composite granules are added into the lunch box mold, and then hot-pressed, cooled and demolded to obtain the bio-based biodegradable lunch box product.

7. The method for preparing a bio-based biodegradable lunchbox material according to claim 6, characterized in that: In step S2, the buffer solution containing carbonic anhydrase is a Tris-HCl buffer with a pH of 7.5-8.5, and the concentration of carbonic anhydrase is 0.5-2 g / L; the soluble calcium salt is calcium chloride or calcium acetate, and the concentration of the calcium salt solution is 0.1-0.5 mol / L; the reaction temperature is 25-40℃, and the reaction time is 2-6 h; furthermore, a soluble organic template agent is added to the reaction system, which is polyaspartic acid or its sodium salt, to induce the directional growth of aragonite-type calcium carbonate whiskers.

8. The method for preparing a bio-based biodegradable lunchbox material according to claim 6, characterized in that: In step S1, the alkaline solution is a sodium hydroxide solution with a mass fraction of 2% to 5%, the treatment temperature is 80 to 90°C, and the treatment time is 1 to 3 hours.

9. The method for preparing a bio-based biodegradable lunchbox material according to claim 6, characterized in that: In S3, the temperature of each section of the twin-screw extruder is 130~160℃, and the screw speed is 150~250rpm; in S4, the hot pressing temperature is 140~170℃, the molding pressure is 8~15MPa, and the holding time is 30~90s.